Factors influencing sexual harassment behavior in sports environment: Evidence from Pakistan - Sarwar, Nabila (Frontiers in Psychology, 2022)
Sexual harassment (SH) in sporting environments has developed as an important field of research. However, a more comprehensive understanding of factors affecting SH behavior is needed. I hypothesized how these effects appear and the scenarios in which they exist. Based on the perspectives of sexual harassment, my study aims to reveal the athletes' perceptions of SH and organizational climate (OC) impact on SH, as well as the mediating mechanisms of low self-esteem (LSE) and moderating role of hostile sexism. Data collected from 435 female football sports clubs in Pakistan, using convenient sampling and using SEM techniques analyze that these factors are related to an increased likelihood of female athlete SH.Our results suggest that athlete perceptions of OC positively predict SH, and OC is positively related to LSE. In addition, LSE positively mediates the effects of athletes’ perceptions of OC on SH. Where hostile sexism strengthens the perceived relationship between OC and LSE, which stimulates the SH of athletes, this paper had deep implications for the literature. It clarified the ways which are crucial for predicting OC. Whether there are written laws on the subject, organizations are reluctant to acknowledge them, which entails developing methods of quantifying SH and creating data accessible to the public. Future study is recommended to evaluate the abuse of power in relation with benevolent sexism to identifying athlete perception of SH .